Alternative fuels for vehicles - Younis , Taha (University of Thi-Qar Journal of Science, 2012)
The purpose of this paper is based on a review of technical literature on the topic of alternative fuel for vehicles (AFVs) which describes the advantages and disadvantages compared to conventional vehicles running on conventional fuels (diesel and gasoline).In addition, the study included the emissions of a fuel cell vehicle (FCV) and internal combustion engine vehicle (ICEV).Global warming; climate change, greenhouse gas (GHG) emissions, and the quality of the air have all been a major concern in the next decades. It is important to identify the major contributors to greenhouse gas emissions in order to develop effective methods and strategies for their reduction. The transportation sector is responsible for a great percentage of the greenhouse gas emissions as well as the energy consumption in the world [18].Ultimately; we will need to replace gasoline with a zero – carbon fuel. All AFVs that have so far been promoted with limited success (electric vehicles, natural gas vehicles, methanol vehicles, and ethanol vehicles) have been each suffered from several of these barriers. Any one from these barriers can be a showstopper from an AFV, even where other clear benefits are delivered.Increasingly alternative economies are being suggested, whereby the growing  energy demand of the future is met with greater efficiency and with more renewable energy sources such as ethanol, methanol, biodiesel, hydrogen, wind, solar and biomass. Hydrogen is being promoted as an alternative energy carrier for sustainable future.